EFFECT OF AGE ON HEARTWOOD / SAPWOOD RELATIONSHIP, EXTRACTIVE CONTENTE, AND PERMEABILITY OF TEAK WOOD - Canal, Wagner Davel; Macedo Ladeira Carvalho, Ana Márcia; Oliveira Carneiro, Angélica de Cássia; Vidaurre, Graziela Baptista; de Freitas, Fabiana Paiva; de Magalhes, Mateus Alves (Floresta, 2020)
Due to the physiological differences in the juvenile and adult phases of teak wood, differentiation occurs in the impregnation by extractive materials along the heartwood regions, assuming that there is also a significant variation in the permeability of this material. Thus, the study aimed to evaluate the influence of age on the heartwood / sapwood ratio (H/S), permeability, and extractives content of Tectona grandis L.f wood. Four ages (10, 12, 14, and 16 years) and four trees (repetitions) were evaluated, totaling 16 samples. The H/S ratio, extractive content, and wood permeability were determined, in addition to the average and maximum permeability among all ages selected for calculation of their porosity. The H/S ratio increased over the ages of 10 and 16, and the content of extractive materials increased until the age of 14. There was a high heterogeneity between the permeability values of the wood at all ages analyzed, and one of the possible explanations for this fact is the presence of tyloses in different places on the trunk and the arrangement of the pores around the growth rings.